2012
DOI: 10.1159/000336297
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Temperature Applied during Gonadal Transformation Leads to Male Bias in Zebrafish <b><i>(Danio rerio)</i></b>

Abstract: Temperature effects on sex determination or differentiation exist in many fish species, with high temperatures predominantly producing more males. The present study aimed at elucidating the genetic background of temperature effects on sex differentiation in zebrafish. Experimental fish were generated by matings between 4 or 6 golden females and a normal or a mitotic gynogenetic male, respectively. All the larvae were reared at 28.5°C until they were divided into 3 groups per full-sib family, a control group ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 105 publications
4
45
0
Order By: Relevance
“…Our results, therefore, emphasize the interplay between genetic and environmental influences and provide a potential explanation for the variable sex ratios observed in zebrafish facilities across the world, which are often unpredictable and biased. The masculinizing effect of elevated temperature confirms previous results in zebrafish (36,39) and correlates with results found in the literature in many other fish species (for reviews, see refs. 16 and 18).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results, therefore, emphasize the interplay between genetic and environmental influences and provide a potential explanation for the variable sex ratios observed in zebrafish facilities across the world, which are often unpredictable and biased. The masculinizing effect of elevated temperature confirms previous results in zebrafish (36,39) and correlates with results found in the literature in many other fish species (for reviews, see refs. 16 and 18).…”
Section: Discussionsupporting
confidence: 90%
“…In domesticated zebrafish, the effects of elevated temperature have been studied after exposure periods concerning embryos (35), juveniles (36,37), or development until adults (38,39). In agreement with the general pattern in fish (18), elevated temperatures result in a higher number of males, although, surprisingly, one study reported more females (40).…”
mentioning
confidence: 78%
“…Answers likely lie in environmental factors and background genetic features that affect the strength of a meiotic oocyte-derived pro-female signal that inhibits oocyte apoptosis, probably by maintaining aromatase production (Slanchev et al 2005;Houwing et al 2007;Wang et al 2007;Siegfried and Nusslein-Volhard 2008;Rodriguez-Mari et al 2010Rodríguez-Marí and Postlethwait 2011;Pradhan et al 2012;Dranow et al 2013). In general, harsh conditions, including high density and poor nutrition, tend to promote male development (Walker-Durchanek 1980;Pelegri and Schulte-Merker 1999;Shang et al 2006;Lawrence et al 2008;Abozaid et al 2011Abozaid et al , 2012Liew et al 2012;Villamizar et al 2012). These harsh factors may act to decrease the pro-female signal by depressing the pool of meiotic oocytes, either by inhibiting primary germ-cell proliferation or entry into meiosis or by promoting oocyte apoptosis.…”
Section: Domesticated Zebrafish Strains Lack a Single Strong Sexlinkementioning
confidence: 99%
“…As expected from the hypothesis that oocyte death is a major feature of zebrafish sex determination, harsh environmental conditions tend to shift sex ratios in favor of males; such factors include gamma rays, hypoxia, high density, high temperature, altered thermocycles, and poor nutrition (Walker-Durchanek 1980;Shang et al 2006;Lawrence et al 2008;Abozaid et al 2011Abozaid et al , 2012Liew et al 2012;Villamizar et al 2012). Zebrafish does not, however, have a typical environmental sex-determination (ESD) mechanism like some sauropsids for which temperature is a cue (Charnier 1966;Lang and Andrews 1994;Merchant-Larios and Diaz-Hernandez 2013;Mork et al 2014).…”
mentioning
confidence: 94%
See 1 more Smart Citation